Characterization of Batrachochytrium dendrobatidis Inhibiting Bacteria from Amphibian Populations in Costa Rica - Madison, Joseph D.; Berg, Elizabeth A.; Abarca, Juan G.; Whitfield, Steven M.; Gorbatenko, Oxana; Pinto, Adrian; Kerby, Jacob L. (Frontiers in Microbiology, 2017)
Global amphibian declines and extinction events are occurring at an unprecedented rate. While several factors are responsible for declines and extinction, the fungal pathogen Batrachochytrium dendrobatidis (Bd) has been cited as a major constituent in these events. While the effects of this chytrid fungus have been shown to cause broad scale population declines and extinctions, certain individuals and relict populations have shown resistance. This resistance has been attributed in part to the cutaneous bacterial microbiome. Here we present the first study characterizing anti-Bd bacterial isolates from amphibian populations in Costa Rica, including the characterization of two strains of Serratia marcescens presenting strong anti-Bd activity. Transcriptome sequencing was utilized for delineation of shifts in gene expression of the two previously uncharacterized strains of S. marcescens grown in three different treatments comprising Bd, heat-killed Bd, and a no Bd control. These results revealed up- and down-regulation of key genes associated with different metabolic and regulatory pathways. This information will be valuable in continued efforts to develop a bacterial-based approach for amphibian protection as well as providing direction for continued mechanistic inquiries of the bacterial anti-Bd response.